In Vitro Synergy of Colistin in Combination with Meropenem or Tigecycline against Carbapenem-Resistant Acinetobacter baumannii - Jacinda C. Abdul-Mutakabbir; Juwon Yim; Logan Nguyen; Philip T. Maassen; Kyle Stamper; Zain Shiekh; Razieh Kebriaei; Ryan K. Shields; Mariana Castanheira; Keith S. Kaye; Michael J. Rybak (MDPI AG, 2021)
Acinetobacter baumannii is currently classified as one of six pathogens that contribute to increased patient mortality. Thus, exploratory studies navigating alternative treatment strategies are of supreme interest. Herein, we completed minimum inhibitory concentration (MIC) testing, and time-kill analyses (TKA) on 50 carbapenem-resistant Acinetobacterbaumannii isolates including 28 colistin-resistant isolates. Upon testing of MEM or TGC in the presence of sub-inhibitory COL against the 50 isolates, there was a median 2-fold reduction in MEM and TGC MICs. In the TKAs, the COL+MEM combination was synergistic in 45 (90%) isolates and bactericidal in 43 (86%) isolates at 24 hours, whereas the COL+TGC combination TKAs demonstrated synergy in 32 (64%) isolates and bactericidal activity was shown in 28 (56%) isolates. Additionally, sulbactam (SUL) and TGC were added to the COL+MEM dual therapy regimen to assess the possible utility of a triple therapy regimen against five non-responsive isolates. The COL+MEM+SUL and COL+MEM+TGC regimens effectively restored synergy in (5/5) 100% of the isolates. The results of this study demonstrate the potential utility of COL combinations in the treatment of carbapenem-resistant isolates.